Molecular characterization of human respiratory syncytial virus strains circulating among hospitalized children in Jordan - Ashraf I. Khasawneh; Nisreen Himsawi; Ashraf Sammour; Hazem Abu Safieh; Salma Burayzat; Hafez Al-Momani; Moureq R. Alotaibi; Sofian Al Shboul; Tareq Saleh (BMC Infectious Diseases)
Abstract Background Human Respiratory Syncytial Virus (HRSV) is a primary cause of severe pediatric respiratory infections, particularly in infants and young children, often resulting in hospitalization. The virus possesses a high degree of mutagenic potential, contributing to significant antigenic diversity, which complicates immune responses and poses challenges for vaccine development and disease management. This study was conducted in Jordan from 2022 to 2023 to epidemiologically determine the prevalence and molecular characteristics of RSV. Methods A total of 288 nasopharyngeal (NP) swabs were collected from hospitalized children at Prince Hamza Hospital, Amman, Jordan. All samples were screened for common viral and bacterial respiratory pathogens using PCR. A partial segment of the G gene of RSV was amplified for molecular characterization and phylogenetic tree analysis. Results Viral and/or bacterial infection was identified in 71.9% (207/288) of the tested specimens. Among these, 35 samples (12.2%, 35/288) tested positive for RSV. Specific subgroup PCR analysis identified (25, 71.4%) RSV-A, (4, 11.4%) RSV-B, and (6, 17.1%) could not be identified using our set of primers. Phylogenetic tree analysis revealed that RSV-A ON1 and RSV-B BA9 genotype strains predominate in Jordan. We observed multiple substitutions in our studied sample which would drive variation in the level of antigenicity and pathogenicity of RSV. Glycosylation sites identified were consistent with previously reported studies. Conclusion This study provides updated epidemiological data on the strains circulating in Amman, Jordan and their molecular characteristics. Continuous RSV surveillance informs vaccine development, guides public health interventions, and enables timely administration of prophylactic treatments, reducing the burden of RSV-related illness.